2020
DOI: 10.1111/dpr.12426
|View full text |Cite
|
Sign up to set email alerts
|

Is development aid securitized? Evidence from a cross‐country examination of aid commitments

Abstract: Motivation How has the securitization of development affected the distribution of bilateral development aid by sector? Over the past two decades, academics and development NGOs have become increasingly concerned about the impact of the securitization of development. This debate has not, however, adequately addressed the impact of securitization on actual aid commitments to key sectors. If aid commitments are influenced by securitization this will have implications for the types of programmes funded by bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
0
8
0
5
Order By: Relevance
“…Since 2000, the UK development policy discourse, in line with that of other traditional bilateral (Lazell & Petrikova, 2020) and multilateral (Petrikova & Lazell, 2017) donors, has become increasingly securitized. A relatively high provision of official development assistance (ODA) has been justified by the need to protect the UK's domestic security from threats posed by fragility and instability | 13 of 42 PETRIKOVA And LAZELL in L&MICs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since 2000, the UK development policy discourse, in line with that of other traditional bilateral (Lazell & Petrikova, 2020) and multilateral (Petrikova & Lazell, 2017) donors, has become increasingly securitized. A relatively high provision of official development assistance (ODA) has been justified by the need to protect the UK's domestic security from threats posed by fragility and instability | 13 of 42 PETRIKOVA And LAZELL in L&MICs.…”
Section: Discussionmentioning
confidence: 99%
“…2 They are also former British colonies. Our previous work has shown that securitization is more prevalent in countries of higher strategic interest to the donor (Lazell & Petrikova, 2020). African countries of lower strategic interest to the UK, for instance former French colonies Mali and Senegal, have had comparatively few aid projects funded by the UK and linked to the security agenda (OECD-Stat, n.d.-a), demonstrating the continent's continued division into its former colonial powers' spheres of influence.…”
Section: Case Selectionmentioning
confidence: 98%
See 2 more Smart Citations
“…Source: Information in this Box is gathered from Kemp (2016 [15]), "OSCE peace operations: Soft security in hard environments", https://www.ipinst.org/wp-content/uploads/2016/06/1606_OSCE-and-Peace-Operations.pdf and (OSCE, 2019 [16]) "Survey of OSCE mission", https://www.osce.org/secretariat/74783?download=true.…”
Section: Box 12 Osce Peace Operations: a Soft Approach To Securitymentioning
confidence: 99%